The Effect of Slape Arrangement On Physical and Mechanical Properties Petung Bamboo Laminate Board (Dendrocalamus asper) - Febriana Tri Wulandari; Habibi Habibi; Raehanayati Raehanayati; Rima Vera Ningsih (Wood Research Journal, 2022)
Wood as a construction material is currently increasingly limited.  One alternative material as a substitute for construction wood is laminated bamboo. Laminated bamboo is a product made from several bamboo slats or bamboo slats that are glued together with the fiber direction parallel to the board with several requirements, among others, must have dimensions of length, width, and thickness that can be converted into boards or blocks. The type of bamboo that will be used in this research is petung bamboo (Dendrocalamus asper). Petung bamboo was chosen because it has a diameter that can reach 20 cm with a wall thickness of 1-3 cm, making it suitable for use as laminated bamboo. The purpose of this study was to determine the effect of blade arrangement on the physical and mechanical properties of petung bamboo laminated boards. The method used in this study is an experimental method with a non-factorial completely randomized design experiment with two treatments and three replications. Based on the results of the study, the arrangement of the laminated board blades did not significantly affect all tests of the physical and mechanical properties of the petung bamboo laminated board. All tests of physical and mechanical properties have complied with JPIC standard No. 1152 2007 except in the MoE test does not meet the standard. Based on the strength class of the laminated board, the bamboo petung laminated board is classified as strong class III which can be used as a protected heavy construction material.